On the track of a Scottish impact structure: a detrital zircon and apatite provenance study of the Stac Fada Member and wider Stoer Group, NW Scotland. (24th April 2019) - Kenny, Gavin G.; O'Sullivan, Gary J.; Alexander, Stephen; Simms, Michael J.; Chew, David M.; Kamber, Balz S.
Abstract: The Stac Fada Member of the Stoer Group, within the Torridonian succession of NW Scotland, is a melt-rich, impact-related deposit that has not been conclusively correlated with any known impact structure. However, a gravity low approximately 50 km east of the preserved Stac Fada Member outcrops has recently been proposed as the associated impact site. We investigate the location of the impact structure through a provenance study of detrital zircon and apatite in five samples from the Stoer Group. Our zircon U–Pb data are dominated by Archaean grains (> 2.5 Ga), consistent with earlier interpretations that the detritus was largely derived from local Lewisian Gneiss Complex, whereas the apatite data (the first for the Stoer Group) display a single major peak at c. 1.7 Ga, consistent with regional Laxfordian metamorphism. The almost complete absence of Archaean-aged apatite is best explained by later heating of the > 2.5 Ga Lewisian basement (the likely source region) above the closure temperature of the apatite U–Pb system ( c. 375–450°C). The U–Pb age distributions for zircon and apatite show no significant variation with stratigraphic height. This may be interpreted as evidence that there was no major change in provenance during the course of deposition of the Stoer Group or, if there was any significant change, the different source regions were characterized by similar apatite and zircon U–Pb age populations. Consequently, the new data do not provide independent constraints on the location of the structure associated with the Stac Fada Member impact event.